The Effects of Minimum Wages on the Health of Working Teenagers - Susan L. Averett; Julie K. Smith; Yang Wang (Institute for the Study of Labor (IZA), 2016)
This paper examines the effect of minimum wage increases on the self-reported health of teenage workers. We use a difference-in-differences estimation strategy and data from the Current Population Survey, and disaggregate the sample by race/ethnicity and gender to uncover the differential effects of changes in the minimum wage on health. We find that white women are more likely to report better health with a minimum wage increase while Hispanic men report worse health.
Keywords: I10; I18; J15; J16; 330; minimum wage; self-reported health; teenagers